Smartphone and Learning: Time Management as a Key Mediator of Negative Effects in High School Students - Efi Yanita Situmorang; Connie Connie; Muhammad Kristiawan (Yayasan Sembilan Pemuda Indonesia, 2026)
The smartphone represents a double-edged sword in education a gateway to infinite knowledge that paradoxically fragments the very attention required for deep learning. This study investigates the direct and indirect effects of smartphone usage intensity on learning effectiveness, with study time management as a mediating variable, among high school students in Bengkulu City, Indonesia. Employing a quantitative mediation design, data were gathered from 75 students (N=75) at Pelita Kasih High School through total sampling. Validated Likert-scale questionnaires assessed all constructs, and hypotheses were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) mediation analysis with bootstrapping (5,000 resamples) in SmartPLS 4.0. Descriptive analysis indicates moderate smartphone usage intensity, alongside high levels of study time management and learning effectiveness. Path analysis reveals that smartphone usage intensity negatively affects learning effectiveness directly (β = -0.337, p < 0.05) and strongly diminishes study time management (β = -0.689, p < 0.001), which positively predicts learning effectiveness (β = 0.520, p < 0.01). The indirect effect (β = -0.358) compounds into a substantial total effect (β = -0.695). With a Variance Accounted For (VAF) of 51.51%, study time management partially mediates this relationship, revealing that over half of smartphone’s detrimental influence operates through disrupted time management. The model explains 62.4% of learning effectiveness variance. These results establish time management as a pivotal buffer against smartphone-induced academic disruption. Practically, this study recommends that schools design comprehensive intervention frameworks integrating digital literacy education with structured time management training, thereby transforming smartphone use from a liability into an educational asset.